Penguatan Karakter dan Kecakapan Abad 21 melalui Pembelajaran Sosial Emosional - Hafizah Hafizah (Jurnal Pendidikan Tuntas, 2025)
Social Emotional Learning (PSE) is an educational approach that emphasizes the development of students' social, emotional and character skills. This review aims to understand the basic concepts of EE, identify the challenges of its implementation in schools, and offer strategic solutions to strengthen the implementation of EE in various educational contexts in Indonesia. The literature review was conducted on accredited national journals in the last ten years with a narrative synthesis approach. The results show that PSE has a positive impact on students' academic achievement and well-being, although it still faces implementation constraints such as limited teacher understanding, resources and policy support. Therefore, strengthening teachers' capacity and integrating PSE in education policy are key.